ҚАРАҚАЛПАҚ ХАЛЫҚ ДӘСТАНЫ «ШАРЬЯР»ДЫҢ ФИЛОЛОГИЯЛЫҚ ҲӘМ ПЕДАГОГИКАЛЫҚ АСПЕКТИНДЕ ҮЙРЕНИЛИЎИНИҢ ГЕЙПАРА МӘСЕЛЕЛЕРИ - Кеңесбаева, Ш.К. (FAN va JAMIYAT, 2020)
The Karakalpak folk epos «Shariyar» is one of the valuable national spiritual heritages of the people. The epos is considered to be an encyclopedical work in which the social-political views of the people, language, history, literature, ethnography and other empiric data about nature and society are reflected. The author of the article analyzes the Karakalpak folk epos «Shariyar» in the aspect of Pedagogical sciences.